Cover Image. (19th September 2018) - Zhou, Wenjing; Wang, Jiwei; Qi, Qichao; Feng, Zichao; Huang, Bin; Chen, Anjing; Zhang, Di; Li, Wenjie; Zhang, Qing; Bjerkvig, Rolf; Li, Xingang; Wang, Jian
Abstract : The cover image, by Wenjing Zhou et al., is based on the Original Research Matrine induces senescence of human glioblastoma cells through suppression of the IGF1/PI3K/AKT/p27 signaling pathway, DOI: 10.1002/cam4.1720 .